Pengenalan Dasar Microsoft Word di Sekolah SDN Blang Keudah - Darmi; Safia Maulida; Zakaria, H.M. Yusuf; Eka Agustina; Maisura; Syahrul (Indo Publishing, 2025)
This article discusses the basic introduction to Microsoft Word as an essential word processing software in the field of education, particularly for students at Blang Keudah Public Elementary School (SDN Blang Keudah). The aim of this introduction is to equip students from grades 4 to 6 with fundamental skills in using Microsoft Word, such as typing, formatting paragraphs, inserting images, and saving documents. In today's digital era, the ability to use software like Microsoft Word is a vital skill that supports the learning process and enhances students' digital literacy from an early age. Through an interactive and hands-on learning approach, students are expected to understand basic functions and apply them to school assignments. This article also highlights the importance of technological infrastructure and the role of teachers in guiding information technology learning at the elementary school level.